Supplementary Data for sepsis timing pre-print - Molly Flint; Fergus Hamilton; David Arnold; David Hettle (Zenodo, 2021)
This repository contains the raw data and code to reproduce the results in the preprint "The timing of use of clinical screening tools affects their ability to predict sepsis mortality. A meta-regression analysis."
by Molly Flint, David Arnold, Fergus Hamilton, and David Hettle
Keywords: sepsis, ews, qSOFA, meta-analysis, meta-regression